Primary hepatic mucosa-associated lymphoid tissue lymphoma in a patient with no chronic liver disease: Case report - Cezar I. Betianu, MD; Augustin Dima, MD; Giorgiana Pavaloiu, MD (Radiology Case Reports, 2017)
Extramarginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) is a non-Hodgkin lymphoma of low-grade malignancy. The most common localization is the stomach, and the common nongastric sites are salivary glands, the skin, orbits, the conjunctiva, the lung, breasts, upper airways, other gastrointestinal sites, and the liver. Primary hepatic MALT lymphoma is a rare disease and the diagnostic can be challenging. The clinical presentation is nonspecific and may range from no symptoms to end-stage liver disease. The radiological aspect of hepatic lymphoma may indicate this diagnosis; however, the final diagnosis is made by hepatic biopsy. We report the case of a 47-year-old woman with no chronic liver disease, incidentally found with a focal liver mass at ultrasound examination. The only clinical symptom was fatigue. The blood tests were normal and tumoral markers were negative. Computed tomography and magnetic resonance imaging were performed. However, because the hepatic lesion was first described as a benign entity and, at second opinion, the suspicion of lymphoma was raised, the patient decided to undergo surgery first, without prior biopsy. The histopathologic analysis confirmed the diagnosis: hepatic MALT lymphoma positive for CD 20 and negative for CD 5, BCL6, cyclin D1, and CD 23. No lymph node involvement was noted and follow-up imaging with positron emission tomography-computed tomography did not show any other site of disease, thus confirming the diagnosis of primary hepatic MALT lymphoma. The aim of this paper was to highlight the imagistic features of primary hepatic lymphoma to contribute to the early diagnosis of this rare disease entity.